2004
DOI: 10.1093/sleep/27.5.923
|View full text |Cite
|
Sign up to set email alerts
|

Using a Wrist-Worn Device Based on Peripheral Arterial Tonometry to Diagnose Obstructive Sleep Apnea: In-Laboratory and Ambulatory Validation

Abstract: In a population of patients suspected of having obstructive sleep apnea, the Watch_PAT can quantify an ODI that compares very well with Medicare criteria for defining respiratory events and an RDI that compares favorably with Chicago criteria for defining respiratory events. The device can be used with a low failure rate for single use in the lab and home for self-administered testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(123 citation statements)
references
References 38 publications
3
117
3
Order By: Relevance
“…Watch-PAT identifi ed the drivers with RDI > 15 with 89.1% sensitivity and 76.9% specifi city. There are studies confi rming the validation of Watch-PAT device simultaneously with PSG, 5,[8][9][10][11][12] detection of the arousals, 6,13 and assessment of CPAP effi cacy. 14,15 This is the fi rst study evaluating the reliability of Watch-PAT in a particular group, in this case, highway bus drivers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Watch-PAT identifi ed the drivers with RDI > 15 with 89.1% sensitivity and 76.9% specifi city. There are studies confi rming the validation of Watch-PAT device simultaneously with PSG, 5,[8][9][10][11][12] detection of the arousals, 6,13 and assessment of CPAP effi cacy. 14,15 This is the fi rst study evaluating the reliability of Watch-PAT in a particular group, in this case, highway bus drivers.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies are with Watch-PAT 100 device. 5,6,[8][9][10][11][12][13][14][15]18,19 Recently, Watch-PAT 200 has been shown to provide quick diagnosis in OSA and to be valid in the diagnosis of OSA during pregnancy. 20,21 Our particular question was the reliability of this device in the diagnosis of obstructive sleep apnea in highway bus drivers.…”
Section: Discussionmentioning
confidence: 99%
“…104 Two cross-over studies randomized patients to home-based PAT, and in-laboratory simultaneous PSG and PAT. 105,106 For comparison to in-laboratory PSG, only the home-based PAT data were used for this recommendation. A single study that evaluated the performance of the PAT device in the home against in-laboratory PSG using a cutoff of AHI ≥ 5, 106 reported a specificity of 0.43 (95% CI: 0.22 to 0.66).…”
Section: Accuracymentioning
confidence: 99%
“…When two studies evaluated the home-based PAT device against in-laboratory PSG at an AHI cutoff of ≥ 15, specificity ranged from 0.77 to 1.00 and sensitivity ranged from 0.92 to 0.96. 105,106 A single study evaluated the PAT device at an AHI cutoff of ≥ 30, and reported a specificity of 0.82 (95% CI: 0.57 to 0.96) and sensitivity of 0.92 (95% CI: 0.62 to 1.00) 105 (see supplemental material, Table S55 through Table S57). …”
Section: Accuracymentioning
confidence: 99%
“…5 It has been shown to accurately detect OSA (in laboratory and ambulatory settings), [5][6][7][8] autonomic arousals, 9 and sleep/wake status. 10 The validity of using PAT and actigraphy signals derived from the PAT recorder to detect REM 11 and light/deep 12 sleep has also been demonstrated in two small studies.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%